Peculiarities of the Implementation of Neologisms in the English Language Internet Discourse - Sadriddinovna, Irgasheva Shokhida (Researchparks Publishing, 2023)
New words and expressions or neologisms are created for new things irrespective of their scale of importance. A large number of new lexical units appeared in connection with the development of computer technology. Neologisms are usually formed under the laws of the relevant language, in his productive patterns of word formation. However, literary books are sometimes created neologisms and unproductive ways of word formation. In such cases, the effective power of word-formation means becomes more clear, vivid, and tangible. Most funds formation of new words so often act as a stylistic device. The attention of linguists is mainly attracted by neologisms related to scientific and technical topics, due to the rapid progress of science and technology in recent decades. This fact had a great impact on the information sphere. It is in the media that all global events occurring in the world are reflected. At the moment, our society is characterized as “informational”, and, therefore, it is based on the processes of collecting, storing and transmitting information, which provides an opportunity for its implementation and further development. The neologisms in the sphere of internet technology are being spread with a high speed to all languages as a result of globalization. Thus, the internet discourse is regarded as one of actual fields of linguistic discourse.